Tanda Vital dan Tingkat Kesadaran Pasien Stroke - Manoppo, Arlien Jeannete; Anderson, Elisa (NUTRIX, 2024)
Blockage or rupture of blood vessels in the brain can cause neurological disorders, such as decreased consciousness. Apart from that, it can also interfere with the regulation of other vital signs, such as body temperature, heart rate, oxygen levels in the blood, and blood pressure. The aim of this study was to analyze the correlation between vital signs and the level of consciousness of stroke patients in the neurology inpatient room. This research used an analytical observational design with a cross sectional approach, involving 82 respondents using convenience sampling techniques. The findings from this study were that the average temperature value (36.6°C), heart rate (81 times/minute), and oxygen levels in the blood of stroke patients (96%) were within normal limits, but the systolic blood pressure value (146) and diastolic (87) on average increased, the GCS assessment of the patient's level of consciousness (11) was still below normal, and there was no significant relationship between vital signs and level of consciousness (p>.05). Recommendations for further research are to increase the sample size and use multivariate analysis for better results. Sumbatan atau pecahnya pembuluh darah di otak dapat menyebabkan gangguan neurologi, seperti penurunan kesadaran. Selain itu, dapat juga mengganggu regulasi tanda vital lainnya, seperti suhu tubuh, denyut jantung, kadar oksigen dalam darah, dan tekanan darah. Tujuan penelitian ini adalah menganalisis korelasi tanda vital dan tingkat kesadaran pasien stroke di ruang rawat inap neurologi. Penelitian ini menggunakan desain observasional analitik dengan pendekatan cross sectional, dengan melibatkan 82 responden melalui teknik convenience sampling. Temuan hasil dari penelitian ini adalah rata-rata nilai suhu: 36,6°C, denyut jantung: 81 kali/menit, dan kadar oksigen dalam darah pasien stroke: 96% berada dalam batas normal, tetapi nilai tekanan darah sistolik: 146 mmHg dan diastolik: 87 mmHg rata-rata mengalami peningkatan dari batas normalnya, penilaian GCS dari tingkat kesadaran pasien: 11 masih di bawah normal, serta tidak ada hubungan yang signifikan antara tanda vital dengan tingkat kesadaraan (p-value > ,05). Rekomendasi bagi penelitian selanjutnya untuk menambah jumlah sampel dan menggunakan analisis multivariat untuk hasil yang lebih baik.